Attitudes before actions: how music teachers’ technological acceptance and competence shape technological behaviour in China - Xiangming Zhang; Andrew King; Helen Prior (Humanities & Social Sciences Communications)
Abstract Technology can be a key aspect in facilitating progress and development in education that sometimes debates the factors that determine the use of technology and its impact on teaching and learning. In education, technology integration can enhance instruction by providing educators with more pedagogical tools, facilitating student learning, and promoting active engagement in the classroom. The Unified Theory of Acceptance and Use of Technology (UTAUT) model has been used to explain teachers’ technology acceptance (TA) and behavioural intentions in this regard. Debate exists as to whether teachers’ technological competence (TC) improves the prediction of technology acceptance behaviour and in particular the factors that influence music teachers’ technology use in China remain unclear. Considering that technological behaviour (TB) usually refers to the actions and decisions of individuals or organisations in using and adopting technological devices, this study examined the relationships between TA, TC, and TB among music teachers in China. Structural equation modelling was employed to analyse data obtained from 307 music teachers in Fujian province, China. The result identified ten influencing factors, which were then grouped into a theoretical framework entitled Technological Competence, Acceptance, and Behaviour (TCAB). This framework describes the factors influencing music teachers’ use of technology from the geographical perspective of China in which TA emerges as a crucial component that directly impacts TB, and TC indirectly affects TB by influencing TA. Although TB is a complex phenomenon that can be influenced by a variety of factors and contexts, the results suggested that music teachers’ attitudes can be a prerequisite for their actions in using technology and reflect the overall enthusiasm of music teachers for using technology in China. The study offers original perspectives on crafting a theoretical model adapted to diverse cultural settings and informs relevant stakeholders to better integrate technology into music education.